Doses, fontes e épocas de aplicação de nitrogênio influenciando teores de clorofila e produtividade do trigo - Theago, Eduardo Quimello [UNESP]; Buzetti, Salatier [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Andreotti, Marcelo [UNESP]; Megda, Marcio Mahmoud [UNESP]; Sabin Benett, Cleiton Gredson (Soc Brasileira de Ciência do Solo, 2014)
To achieve high wheat yield, correct management of N fertilization and the use of high yield potential cultivars are necessary. The aim of this study was to evaluate the effects of different application rates and sources of N, applied totally at sowing or in topdressing, on grain yield and yield components of two irrigated wheat cultivars under a no-till system, grown in a Cerrado (Brazilian tropical savanna) region of low altitude. A randomized block design was used in a 5 x 3 x 2 x 2 factorial arrangement with three replications, combining five levels of N (0, 50, 100, 150, and 200 kg ha(-1)), three sources of N (Entec (R), ammonium sulfate, and urea), and two application times (at sowing, near the rows, or in topdressing) in two wheat cultivars (IAC 370 and Embrapa 21). The wheat cultivars had similar grain yields. There was no difference among the sources of N for grain yield and yield components. The N applied totally at sowing did not differ from the traditional application at sowing and in topdressing for production of irrigated wheat in no-tillage. The increase in application rates of N increased the leaf N contents and chlorophyll, plant height, and the number of ears per m(2). Grain yield of the wheat cultivars IAC 370 and Embrapa 21 increased up to the application rates of 134 and 128 kg ha(-1) of N, respectively, regardless of application time and source of N. The positive correlation between chlorophyll leaf content and grain yield in accordance with N fertilization levels indicates that N fertilization in topdressing can be recommended based on SPAD readings of leaf chlorophyll performed at 38 days after wheat plant emergence.
Nitrogen application rates, sources, and times affecting chlorophyll content and wheat yield
Keywords: Triticum aestivum L.; Nitrogen fertilization; Cerrado; no-tillage; Winter cereal crops; Triticum aestivum L.; Adubação nitrogenada; Cerrado; Cereais de inverno; Plantio direto